Development of Ekoterin E-Modules to Improve Learning Outcomes of Fifth Grade Elementary School Students - Ahmad Syukur; Yuni Ratnasari; Henry Suryo Bintoro; Nanthini Jayaram (Jurnal Pendidikan Sains Indonesia, 2025)
The low achievement of Indonesian students in science and numeracy, as reflected in the 2022 PISA results, highlights limited innovation and weak integration of numeracy in elementary science learning. Classroom observations at SDN 2 and SDN 1 Kalipucangwetan further revealed conventional, teacher-centered learning with minimal use of digital media. This study aimed to develop and evaluate the effectiveness of the ekoterin e-module an ecosystem-based digital learning module integrated with numeracy to improve fifth grade students learning outcomes in the IPAS subject. Using the research and development (RD) method with the ADDIE model (analysis, design, development, implementation, and evaluation), data were collected through interviews, observations, questionnaires, and pretestposttest assessments. The e-module was designed using canva for website, converted into an android application, and equipped with interactive multimedia such as videos, games, and quizzes. Expert validation yielded an average feasibility score of 94.6% (very feasible), while teacher and student practicality tests scored 95.58% (very practical). Effectiveness testing, analyzed using a quasi-experimental design, showed a significant difference (p 0.001) between the experimental group (mean = 81.71; N-Gain = 0.56) and the control group (mean = 72.56; N-Gain = 0.36). These findings indicate that the ekoterin e-module is valid, practical, and effective in improving students IPAS learning outcomes, particularly in understanding ecosystem concepts and integrating numeracy in science learning